Power and status across cultures. (June 2020) - Torelli, Carlos J; Leslie, Lisa M; To, Christopher; Kim, Sahoon
Highlights: Culture affects how status and power are conceptualized, who attains them, and their effects. In individualistic cultures, power is conceptualized in personalized terms (self-focused). In collectivistic cultures, power is conceptualized in socialized terms (other-focused). Abstract : This article synthesizes recent psychological research at the intersection of power, status, and culture. Our review shows that culture affects how status and power are conceptualized, who attains them, and what their consequences are. In individualistic cultures (and particularly vertical ones that emphasize hierarchical arrangements), power is conceptualized in personalized terms (i.e. focus on self-benefits), competence drives status attainment, norm violations increase power, and individuals strive primarily for power, approve of powerholders that behave equitably, and feel happy when they have personal power. In contrast, in collectivistic cultures (and particularly horizontal ones that promote egalitarianism), power is conceptualized in socialized terms (i.e. focus on benefitting others), warmth and competence drive status attainment, norm adherence increases power, and individuals strive primarily for status, approve of powerholders that behave compassionately, and feel happy when they have socialized power. We discuss what remains unknown as a mechanism for guiding future work.